(untitled) (Bangladesh Journal of Child Health, 2018)
Background: The normal hematological values in newborns differ significantly from those of infants, older children and adults. In our observation, the values of the newborn babies vary according to the gestational age. At birth the hemoglobin, hematocrit, mean corpuscular volume and mean corpuscular hemoglobin of term newborns are significantly higher than those of older infants and children, and in preterm newborns the differences are even more pronounced. The objective of this study is to evaluate the erythrocyte indices in preterm and term newborns at birth. Methodology: This cross sectional study was conducted in the department of Neonatology in BSMMU from May 2014 to April 2015. A total of 86 newborns; 48 term and 38 preterm were included in the study. Newborns were divided into two groups- term group and preterm group. Erythrocyte indices: hemoglobin (Hb), hematocrit (Hct), red blood cell (RBC) count, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red cell distribution width (RDW) were estimated from cord blood immediately after birth. Results: Mean hemoglobin level in term group was 15.65±1.04g/dl and preterm group was 15.21±0.93g/dl; this difference was statistically significant (p<0.05). Mean hematocrit value was significantly higher in term group (47.27%) than preterm group (46.10%) (p< 0.05). Mean MCH in term group was 34.49 pg and preterm group was 35.83 pg; this difference was statistically significant (p<0.05). Mean RBC count in term group was 4.47 million/cmm and preterm group was 4.35 million/cmm. Mean MCV was higher in preterm group (107.70 fl) than term group (104.58 fl): Mean MCHC was higher in preterm group (33.34g/dl) than term group (33.0g/dl); Mean RDW in term group was 18.18% and in preterm group was 18.58%. These differences were not statistically significant (p>0.05). Conclusion: This study concluded that erythrocyte indices of all newborns are not same; these differ according to gestational age. Bangladesh J Child Health 2018; VOL 42 (2) :58-61